THE JOGO-GO-GO MUST GO ON - THE CONSTRUCTION OF A TRAGIC-FARSICAL INTERPELATION IN CONTEMPORARY URBAN PERFORMANCE: the example of Hasard performed by Erro Grupo - Baumgärtel, Stephan Arnulf; Marengo, Mayana (Sala Preta, 2014)
The following paper analyses the performance strategies used by Brazilian theater and performance group ERRO GRUPO in their intervention Hasard , to interpelate the spectators and to place them critically both within the theatrical game as well as the urban environment. We part form the hypothesis that ERRO Group´s interventions pick as their central theme the profound crisis of democracy and its social relations in face of the hegemony of economic relations in a capitalist society. We perceive this link between theatrical and social crisis especially in the way how Hasard qualifies the participation of the spectators. The role of the spectators is modeled as to oscilate paradoxically between the raison-d’etre of the game and a function effectively rendered unconsequential for the game to happen and to continue. This oscilation is a significant contradiction, for it takes the spectator to experience and possibly live through what can be called a political experience of tragic-farsical dimensions.